A rare benign ovarian tumour. (1st March 2016) - Morna Palmeiro, Marta; Cunha, Teresa Margarida; Loureiro, Ana Luisa; Esteves, Gonçalo
Abstract : Sclerosing stromal tumour (SST) of the ovary is an extremely rare and benign ovarian neoplasm, accounting for 6% of the sex cord stromal ovarian tumours subtype. Usually, it is found during the second and third decades of life. Patients commonly present with pelvic pain, a palpable pelvic mass or menstrual irregularity. We report a case of a 20-year-old woman reporting of mild pelvic pain, with normal laboratory data. On imaging examinations, a large right adnexal tumour was found, with features suggesting an ovarian sex cord tumour. The patient underwent right salpingo-oophorectomy, diagnosing a SST of the ovary. This paper also reviews the literature, and emphasises the typical pathological and imaging characteristics of these rare benign ovarian lesions, and their impact, in a conservative surgery.